Visual Social Semiotics on Malaysian Fishing Boat Capture News - Bonaventura Satya Bharata; Nik Norma Nik Hasan; Azrina Husin (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
Indonesia-Malaysia is two neighboring countries in Southeast Asia. The geographical proximity makes the two countries have a lot in common. However, this similarity does not guarantee that the two countries can coexist harmoniously. One of the problems in the relationship between the two countries is border-related issues, such as illegal fishing in the border area. This issue has been widely covered by the Indonesian mass media, including Metro TV and TVRI. This paper tries to see how Metro TV and TVRI reported the arrest of a Malaysian fishing boat near the border. This study uses a semiotic social visual analysis as a research method and the main theory of social reconstruction of reality. The research findings show Metro TV interprets this incident as illegal fishing and sovereignty violations. Meanwhile, TVRI interpreted this incident as illegal fishing and the achievements of the Indonesian marine police.